The impact of the increased voltage in the catenary constant current by the amount of energy losses - Mukha, A. M.; Baliichuk, O. Yu. (Science and Transport Progress, 2010)
In the article the results of study of the influence of rising the voltage in DC contact network on the value of losses in this contact network are presented. The calculations are executed with use of traditional commonly accepted techniques.